Nation, Language, Islam - Helen M. Faller (Central European University Press, 2011)
A detailed academic treatise of the history of nationality in Tatarstan. The book demonstrates how state collapse and national revival influenced the divergence of worldviews among ex-Soviet people in Tatarstan, where a political movement for sovereignty (1986-2000) had significant social effects, most saliently, by increasing the domains where people speak the Tatar language and circulating ideas associated with Tatar culture. Also addresses the question of how Russian Muslims experience quo...